(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article describes the role of the communicative skills of future pilots in the context of their readiness to solve problematic situations that may arise in the professional activities of flight personnel. Statistics show that it is precisely because of errors in activities that are associated with decision-making occur the largest number of accidents. This is evidence that the current pilot, for the most part, does not fully meet the modern requirements for the operation of aircraft. And although the flight institutions, in general, perform their functions of training pilots, the system of professional training that built mainly on the basis of the experience of the flight methodological work of its developers, often has no scientific justification and is not optimal. As a result, the cadets have not sufficiently formed the skills that contribute to their readiness to make a competent decision in a problem situation that arise during training flight. In this regard, the professional training of future pilots needs to revise a number of basic provisions. The authors provided definitions for such concepts as "skill", "communication skills" and "readiness of future pilots to solve problem situations", which reveal their essence and emphasize the feature of professional training of aviation specialists. The article focuses on the need to optimize the system of professional training of future pilots, which should contribute to the formation of readiness to solve problematic situations of professional activity.